Analysis of Employee Performance Improvement in Medan City PUD Market - Benhur Pakpahan; Bernadetta A. J. Simbolon; Rehulina Bangun; Tosanov TP Napitupulu; Darmawati Simanjuntak (Syntax Corporation Indonesia, 2022)
The achievement of revenue targets for PUD (Regional Public Enterprises) Market of Medan was not as expected, which shows the performance of PUD Market of Medan is not optimal. Many factors affect the achievement of revenue targets, one of which is the human factor, in this case, is the absence of PUD Market employee performance. If the employee has a good performance, then thetrader as the party renting selling space will be more loyal and impact increasing the occupancy rate of the market. This study aims to analyze PUD Market of Medan employee performance and its influence factor. This type of research in this study is correlational researchconsisting of four independent variables and the dependent variable of employee performance. Analysis of the data used is multiple regression analysis. The result showed that the performance of employees PUD Market in Medan by 39.1% was influenced bycompetence, work culture, organizational communication, and motivation.